2014
DOI: 10.3998/ark.5550190.p008.482
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of furan substituted dihydrofuran compounds by radical cyclization reactions mediated by manganese(III) acetate

Abstract: In this study, novel furan substituted dihydrofuran compounds were synthesized by the radical addition of 1,3-dicarbonyl compounds to 1,1-and 1,2-disubstituted alkenes using manganese(III) acetate in HOAc. It is observed that 1,1-disubstituted alkenes gave better yields whereas 1,2-disubstituted alkenes gave moderate yields. Besides, 1,2-disubstituted alkenes gave us cisisomers whereas trifluoromethylated 1,3-dicarbonyl compounds with 1,2-disubstituted alkenes gave us trans-isomers of dihydrofuran determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…AChE (from electric eel, type V-S), acetylthiocholine iodide (ATCI), 5,5′-dithiobis(2nitrobenzoic acid) (DTNB) were supplied from Sigma Aldrich. Radical oxidant Mn(OAc)3 was synthesized by electrochemical method [43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AChE (from electric eel, type V-S), acetylthiocholine iodide (ATCI), 5,5′-dithiobis(2nitrobenzoic acid) (DTNB) were supplied from Sigma Aldrich. Radical oxidant Mn(OAc)3 was synthesized by electrochemical method [43].…”
Section: Methodsmentioning
confidence: 99%
“…Manganese(III) acetate [33][34][35][36][37] and Cerium(IV) ammonium nitrate [38][39][40] are the most widely used transition metal salts in this reaction. Our research group has reported the synthesis of dihydrofuran compounds by the radical cyclization of 1,3-dicarbonyl compounds with various unsaturated systems such as aromatic conjugated alkenes [41,42], dienes [43,44] and conjugated amide derivatives [45,46] mediated by Manganese(III) acetate and Cerium(IV) ammonium nitrate.…”
Section: Introductionmentioning
confidence: 99%
“…further explored the manganese(III) acetate mediated radical addition reaction of trifluoromethyl‐β‐dicarbonyl compounds 1 with various substituted alkenes 32 , 34 and 36 , leading to the formation of dihydrofuran derivatives of type 33 , 35 and 37 , respectively (Scheme 10). [82–84] Notably, trans ‐isomers 37 were obtained in the reaction of trifluoromethyl‐β‐dicarbonyl compounds 1 with various 1,2‐disubstituted alkenes 36 . Reaction of 1 with 2‐thienyl and 2‐furyl substituted alkenes 28 led to the synthesis of dihydrofurans containing trifluoromethyl ketone 29 and trifluoromethyl group 31 [85] .…”
Section: Trifluoromethyl‐β‐dicarbonyls Based Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Similarly, aldehydes, ketones, monocarboxylic acids and their anhydrides, β-dicarbonyl compounds (such as β-diketones), β-keto esters, β-keto carboxylic acids and amides, malonic acid and its derivatives, and β-nitro carbonyl compounds are oxidized by manganese(III) acetate to attain a variety of products [15]. Manganese(III) mediation in reactions not only provides oxidative cyclization [16][17][18][19][20][21][22][23][24][25][26][27][28][29], but also enables highly diversified acetoxidation [30][31][32][33][34], halogenation [35,36], aromatization [37][38][39], oxidation [40,41], phosphonation [42,43], epoxidation [44], and also polymerization [45]. Cyclization occurs via two different mechanisms: intermolecular and intramolecular.…”
Section: Introductionmentioning
confidence: 99%